The therapeutic abortion or any type of abortion, is it a matter of personal decision in the search for the welfare? Psychological aftermath - Fernández Díaz, Edulgerio (2015)
This research was carried out in order to know and analyze the psychological and moral aftermath that abortion leaves on those women who practiced it. To do this, different references that have tackled this problem in different social and cultural contexts were examined. In order to present a research easier to read and understand, this work has been structured in three themes. First, the psycho-emotional effects of abortion are studied; where it will be discovered that abortion leaves aftermaths on woman’s life. Secondly, symptoms about flashback of the abortion are analyzed, discovering that the experience of the loss of a human life leads to experiencing a series of psychopathological symptoms. And thirdly, we address the approaches that life sciences present about the human embryo to discover that an intrinsic ontological statute assists the human life, that is, with a value in itself, independently from the human criterion and the way how it has been conceived.